Three-dimensional FSI Simulation by Using a Novel Hybrid Scaling – Application to the Tacoma Narrows Bridge - Szabó, Gergely; Györgyi, József; Kristóf, Gergely (Periodica Polytechnica Civil Engineering, 2020)
In this paper a novel fluid-structure interaction approach for simulating flutter phenomenon is presented. The method is capable of modelling the structural motion and the fluid flow coupling in a fully three-dimensional manner. The key step of the proposed FSI procedure is a hybrid scaling of the physical fields; certain properties of the CFD simulation are scaled, while those of the mechanical system are kept original. This kind of scaling provides a significant speedup, since the number of the costly CFD time steps can be remarkably reduced. The acceptable computational time makes it possible to consider complex engineering problems such as buffeting, vortex shedding or flutter of a bridge deck or a wing of an airplane.